SYSTEMATIC LITERATURE REVIEW KERENTANAN LANSIA TERHADAP SERANGAN PHISHING PADA SISTEM DANA PENSIUN DIGITAL - Hanacahyani Widya Asih; Lintang Amarul Fatah; Mukti Diananingsih; Djoko Pitoyo; Eka Ardhianto; Aji Supriyanto (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The digital transformation of financial systems has improved efficiency while simultaneously expanding the cybersecurity attack surface, particularly for phishing threats in pension fund distribution. Elderly individuals, as primary beneficiaries, are considered highly vulnerable due to limited digital literacy, cognitive decline, and a strong trust bias toward authority. This study aims to identify phishing attack patterns, risk factors, and effective mitigation strategies targeting elderly populations through a Systematic Literature Review (SLR) approach following the PRISMA framework. Literature was sourced from IEEE Xplore, Scopus, SpringerLink, and Google Scholar (2015–2025). A total of 120 articles were initially identified, with 35 studies meeting the inclusion criteria after rigorous screening. The findings indicate that elderly individuals are particularly susceptible to email phishing, smishing, and vishing, with significantly higher success rates compared to younger populations. Key contributing factors include low cybersecurity literacy, cognitive limitations, trust bias, and non-inclusive interface design. Effective mitigation strategies include user-centered security design, biometric multi-factor authentication (MFA), and simulation-based security training. This study contributes to a comprehensive risk mapping of phishing threats among elderly pension beneficiaries and provides actionable insights for designing more secure and inclusive digital pension systems.